TEACHING THE SUBJECTS OF "MICROBIOLOGY AND VIROSOLOGY" IN MEDICAL INSTITUTES WITH THE HELP OF A PERSONALIZED LEARNING PLATFORM BASED ON ARTIFICIAL INTELLIGENCE - Abdullayev G‘oyibsher Abdulxamidovich (Modern American Journals, 2025)
Microbiology and virology are disciplines of high scientific and practical importance in the fields of biology, medicine, sanitation, biotechnology and public health. The educational process in these areas includes complex theoretical concepts and experimental basic concepts.